Ao haru ride. Volume 2 - Sakisaka, Io (Shojo beat manga., 2018)
Futaba Yoshioka has encountered her first love again in high school, but he seems different from the boy she once knew. Kou has confessed to Futaba that in junior high he liked her too, but he believes they can never return to those times. Kou continues to act both brusque and sweet. Will a leadership retreat bring them closer together?